Development and validation of a UPLC-MS/MS method for simultaneous detection of doxorubicin and sorafenib in plasma: Application to pharmacokinetic studies in rats - Alanoud Altalal; Aliyah Almomen; Musaed Alkholief; Ziyad Binkhathlan; Nourah Z. Alzoman; Aws Alshamsan (Elsevier, 2023)
An ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was developed for the simultaneous quantitation of doxorubicin (DOX) and sorafenib (SOR) in rat plasma. Chromatographic separation was performed using a reversed-phase column C18 (1.7 μm, 1.0 × 100 mm Acquity UPLC BEH™). The gradient mobile phase system consisted of water containing 0.1% acetic acid (mobile phase A) and methanol (mobile phase B) with a flow rate of 0.40 mL/min over 8 min. Erlotinib (ERL) was used as an internal standard (IS). The quantitation of conversion of [M + H]+, which was the protonated precursor ion, to the corresponding product ions was performed using multiple reaction monitoring (MRM) with a mass-to-charge ratio (m/z) of 544 > 397.005 for DOX, 465.05 > 252.03 for SOR, and 394 > 278 for the IS. Different parameters were used to validate the method including accuracy, precision, linearity, and stability. The developed UPLC-MS/MS method was linear over the concentration ranges of 9-2000 ng/mL and 7-2000 ng/mL with LLOQ of 9 and 7 ng/mL for DOX and SOR, respectively. The intra-day and inter-day accuracy, expressed as % relative standard deviation (RSD%), was below 10% for both DOX and SOR in all QC samples that have drug concentrations above the LLOQ. The intra-day and inter-day precision, expressed as percent relative error (Er %), was within the limit of 15.0% for all concentrations above LLOQ. Four groups of Wistar rats (250-280 g) were used to conduct the pharmacokinetic study. Group I received a single intraperitoneal (IP) injection of DOX (5 mg/kg); Group II received a single oral dose of SOR (40 mg/kg), Group III received a combination of both drugs; and Group IV received sterile water for injection IP and 0.9% w/v sodium chloride solution orally to serve as a control. Non-compartmental analysis was used to calculate the different pharmacokinetic parameters. Data revealed that coadministration of DOX and SOR altered some of the pharmacokinetic parameters of both agents and resulted in an increase in the Cmax and AUC and reduction in the apparent clearance (CL/F). In conclusion, our newly developed method is sensitive, specific, and can reliably be used to simultaneously determine DOX and SOR concentrations in rat plasma. Moreover, the results of the pharmacokinetic study suggest that coadministration of DOX and SOR might cause an increase in exposure of both drugs.